2021
DOI: 10.1093/eep/dvab005
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation at birth potentially mediates the association between prenatal lead (Pb) exposure and infant neurodevelopmental outcomes

Abstract: Early-life lead (Pb) exposure has been linked to adverse neurodevelopmental outcomes. Recent evidence has indicated a critical role of DNA methylation (DNAm) in cognition, and Pb exposure has also been shown to alter DNAm. However, it is unknown whether DNAm is part of the mechanism of Pb neurotoxicity. This longitudinal study investigated the associations between trimester-specific (T1, T2, and T3) maternal blood Pb concentrations, gene-specific DNAm in umbilical cord blood, and infant neurodevelopmental outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…There have been many studies focusing on the relationships between environmental exposures and neurodevelopmental outcomes through DNA methylation. Some studies considered one single exposure and one single outcome (Engdahl et al, 2021); some studies considered one single exposure and multiple outcomes (Rygiel et al, 2021); while some studies considered multiple exposures and one single outcome (Cadiou et al, 2020). Our research is distinct from these existing studies in that we simultaneously consider a spectrum of exposures and a spectrum of correlated cognitive, behavioral, and mental health problems outcomes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There have been many studies focusing on the relationships between environmental exposures and neurodevelopmental outcomes through DNA methylation. Some studies considered one single exposure and one single outcome (Engdahl et al, 2021); some studies considered one single exposure and multiple outcomes (Rygiel et al, 2021); while some studies considered multiple exposures and one single outcome (Cadiou et al, 2020). Our research is distinct from these existing studies in that we simultaneously consider a spectrum of exposures and a spectrum of correlated cognitive, behavioral, and mental health problems outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…Prior studies have focused on a single exposure or a single outcome. For example, a recent study showed that DNA methylation partly mediates the association between Bisphenol F (BPF) exposure and lower cognition in boys (Engdahl et al, 2021); another study showed that DNA methylation mediated the association between early-life lead (Pb) exposure and infant neurodevelopmental outcomes such as psychomotor development index and rating scale of emotional regulation (Rygiel et al, 2021). Similarly, another study considered a single outcome, body mass index (BMI), and a spectrum of exposures, with the goal of examining whether DNA methylation mediates the relationship between an array of environmental exposures and BMI (Cadiou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with 10 μg/g Pb in the maternal patella was significantly associated with 0.61% higher methylation of IGF2 and sex‐specific 0.23% higher methylation of HSD11B2 among the female offspring (Goodrich et al, 2015). Recently, a study on the ELEMENT cohort mentioned direct evidence of prenatal Pb exposure and higher methylation patterns at CCSER1 (Rygiel et al, 2021). A different cohort study conducted on 127 pregnant mothers recruited in MINIMat food and supplementation in rural Bangladesh determined the Pb concentration in the urine (gestational week 8) and erythrocytes (gestational week 14) (Engström et al, 2015).…”
Section: Pb‐mediated Epigenetic Modifications In Fetal Bodymentioning
confidence: 99%
“…Low levels of Pb exposure in early childhood resulted in delayed neurodevelopment in the first 7 years of life (Baghurst et al, 1992). In epidemiological cohort studies, Pb exposure during pregnancy was found to induce DNA methylation at the CpG locus, leading to impaired cognitive function in infants, with the most favorable evidence being DNA methylation of two genes, GCNT1 and CCSER1, suggesting that altered DNA methylation levels mediate the association between prenatal lead exposure and neurodevelopmental outcomes in infants (Rygiel et al, 2021). Hong et al (2021) found that the DNA methylation levels of HCP, ICP, and LCP in the chromosomal CpG region of rats exposed to Pb during pregnancy were higher than those of controls, and the methylation levels of BP‐, CC‐, and MF‐related genes were lower in the experimental group than in the control group, which indicated that maternal Pb exposure leads to impaired learning and memory functions in the offspring.…”
Section: Pb‐mediated Dna Methylation In Neurological Disordersmentioning
confidence: 99%